Determinants of Female Labor Force Participation Rate: Evidence from Indonesia - Pramudya, Mandala Eka; Abidin, Ali Zainal (Lembaga Riset Ilmiah, 2025)
This study analyzes the determinants of the female labor force participation rate (FLPR) in Indonesia during the period 2018-2023 using a panel data approach and Fixed Effects model. The variables analyzed include the Gender Development Index (GDI), Provincial Minimum Wage (WAGE), fertility rate, women's involvement as formal labor, and women's representation in parliament. The results show that the GDI, WAGE, and women's involvement in formal labor contribute positively to the increase in FLPR. In contrast, high fertility rates and women's representation in parliament have a negative impact on women's participation in the labor market. These findings indicate that improving women's access to education, fairer wage policies, and better reproductive health services can increase women's involvement in the national economy. In addition, this study reveals that women's role in politics has not fully positively impacted their participation in the workforce, suggesting the need for more effective affirmative policies.